Improving Solar Cell Performance with High-Efficiency Infrared Quantum Cutting in Tb3+−Yb3+ Codoped Silica Hafnia Glass and Glass-Ceramic Thin Films - Lamyae Oulmaati; Salima El Amrani; Khalid Bouziane; Adel Bouajaj; Mohammed Reda Britel; Francesco Enrichi; Maurizio Ferrari (Applied Sciences, 2023)
An efficient quantum cutting mechanism was observed in a system comprising <semantics>Tb3+−Yb3+</semantics> codoped silica hafnia glass and glass-ceramic. Thin films were deposited on silicon substrates using the dip-coating method and photoluminescence dynamics revealed a quantum efficiency of up to 179% at 980 nm. These films can efficiently convert light to lower energy levels and can easily be integrated into silicon-based solar cells, increasing their photoelectric conversion efficiency at a low cost. This was demonstrated through electrical characterization, which revealed a boost in solar cell efficiency when the film was utilized. It was specifically noted that the efficiency of Si solar cells increased by 10.79% and 10.78% when covered with 70SiO2<semantics>−</semantics>30HfO2<semantics>−3Tb3+−12Yb3+</semantics> glass and glass ceramic, respectively. Furthermore, an evaluation of the additional external quantum efficiency, derived from this optical system, revealed an improvement ranging from 2.64% to 3.44%. This finding highlights the enhanced light conversion capabilities of the quantum cutting mechanism within the system.